EVOLUTION OF CONSCIOUSNESS: THE MULTISUBSTANTIAL EVOLUTION OF THE OBSERVER AND THE HIERARCHY OF MODAL LOGICS IN CAUSAL DUALISM/EVOLUÃÃfO DA CONSCIÃNCIA: A EVOLUÃÃfO MULTISUBSTANCIAL DO OBSERVADOR E A HIERARQUIA DA LÃ"GICA MODAL NO DUALISMO CAUSAL - Safronov, Alexey Vladimirovich (Synesis, 2022)
The subject of the author's research is the existing and possible theories describing the development or evolution of such a mental phenomenon as consciousness. The main approaches to the formation of such theories in their historical perspective have been considered. In particular, the currently relevant theory of integrated information by Tononi combines the idea of panpsychism about the fundamental role of the mental and the theory of evolution by Spencer about the increasing level of complexity in the world. The evolutionary theories of Dennett and Dawkins are based on the Darwinian idea of natural selection. The periodization of cultural and historical stages in the development of mankind and, as a consequence, the types of human thinking by Jaspers continues the tradition of Hegel's historicism and the isolation of the spiritual principle in the development of man by Dilthey. An approach to the evolution of consciousness within the framework of causal dualism has also been considered. The article proposes a thought experiment in which the ancient Greek philosopher Socrates is transferred to the present. The question of how a philosopher would perceive the type of thinking and consciousness of a modern person has been investigated. It has been concluded that Socrates belongs to a certain type of thinking corresponding to his historical period of the evolution of thinking and consciousness. Keywords: Socrates. Causal dualism. Pluralism. The evolution of consciousness. The evolution of thinking. Hierarchy of logics. Statement of observability. Statement of causality. O tema da pesquisa do autor Ã© as teorias existentes e possÃveis descrevendo o desenvolvimento ou evoluÃ§Ã£o de um fenÃ´meno mental como a consciÃªncia. As principais abordagens para a formaÃ§Ã£o de tais teorias em sua perspectiva histÃ³rica tÃªm sido consideradas. Em particular, a teoria da informaÃ§Ã£o integrada atualmente relevante de Tononi combina a idÃ©ia de panpsicismo sobre o papel fundamental do mental e a teoria da evoluÃ§Ã£o de Spencer sobre o crescente nÃvel de complexidade no mundo. As teorias evolutivas de Dennett e Dawkins sÃ£o baseadas na idÃ©ia darwiniana de seleÃ§Ã£o natural. A periodizaÃ§Ã£o dos estÃ¡gios culturais e histÃ³ricos no desenvolvimento da humanidade e, como conseqÃ¼Ãªncia, os tipos de pensamento humano por Jaspers continua a tradiÃ§Ã£o do historicismo de Hegel e o isolamento do princÃpio espiritual no desenvolvimento do homem por Dilthey. Uma abordagem da evoluÃ§Ã£o da consciÃªncia dentro da estrutura do dualismo causal tambÃ©m foi considerada. O artigo propÃµe uma experiÃªncia de pensamento na qual o antigo filÃ³sofo grego SÃ³crates Ã© transferido para o presente. A questÃ£o de como um filÃ³sofo perceberia o tipo de pensamento e consciÃªncia de uma pessoa moderna tem sido investigada. Concluiu-se que SÃ³crates pertence a um certo tipo de pensamento correspondente ao seu perÃodo histÃ³rico de evoluÃ§Ã£o do pensamento e da consciÃªncia. Palavras-chave: SÃ³crates. Dualismo causal. Pluralismo. A evoluÃ§Ã£o da consciÃªncia. A evoluÃ§Ã£o do pensamento. Hierarquia da lÃ³gica. DeclaraÃ§Ã£o de observabilidade. DeclaraÃ§Ã£o de causalidade.